(untitled) (Third Sector Social Economic Review, 2023)
In the aviation sector, where we consider the sum of all the elements used for the aviation field, consumers are able to meet their transportation needs quickly and comfortably by flying. Organizational justice, which is the situation in which the decisions and practices of the managers about the organization and its employees are perceived positively by the employees, is an important area for the companies working in this business field. In social media, which is known as an interactive communication platform where consumers produce content using the internet, businesses promote their services. Personification of the brand as an individual, which will enable to distinguish the service or product offered by a business from another, is the personification of the brand. The aim of this study is to investigate the effect of organizational justice on the brand personality of social media marketing among employees in the business. For the quantitative research to be carried out for this purpose, the data obtained as a result of the application of the survey form created in the Google form were analyzed through the SPSS 2.5 program. Our hypotheses put forward in line with the model created as a result of the t-test and ANOVA test applied here were tested. As a result, it has been concluded that the brand personality that businesses create by using social media marketing has a positive and significant effect on the organizational justice of the managers in the organization. The application of this study in the production sector and the comparison of the results will contribute to the generalization of the study.